Integrating Buddhist values into educational management: The role of self-management in enhancing educational motivation in inland Buddhist communities - Burmansah, Burmansah (Journal of Educational Management and Instruction (JEMIN), 2025)
This study explores the intersection of educational management, societal life, and educational motivation within inland Buddhist communities in Lampung and South Sumatra Provinces, Indonesia. It examines how these communities integrate their cultural and religious identities into educational practices and management, shaping their motivation for learning despite geographical and motivational challenges. The Buddhist way of life, rooted in the teachings of the Buddha, fosters self-management and mindfulness, which influence their educational aspirations. Living in isolated inland settlements, these communities develop unique self-management skills through practices like six concords and mindfulness, which enhance their capacity for education. A quantitative survey method was employed, involving 210 respondents selected based on specific quality criteria. Data were collected using questionnaires and analyzed through path analysis with SPSS 26. The findings reveal significant relationships between mindful living, the six Buddhist concords, self-management, and educational motivation. The study underscores that integrating community life situations, cultural values, and Buddhist teachings into educational management policies can enhance educational motivation. The research suggests that education policies should align with societal contexts to promote higher education standards while fostering self-management skills. By leveraging Buddhist principles and mindfulness, these communities can transform their views on education, overcoming barriers associated with their geographic and motivational constraints. This study highlights the role of cultural and religious values in educational development and provides actionable recommendations for tailoring educational management to community needs, fostering societal progress and deeper engagement with education.